FM sequence optimisation of chaotic‐based random stepped frequency signal in through‐the‐wall radar. Issue 7 (1st September 2017) - Quan, Yinghui; Li, Yachao; Hu, Wen; Zhai, Yadi; Xing, Mengdao
Abstract : Chaotic‐based random stepped frequency signal is applied in the multiple‐input‐multiple‐output through‐the‐wall detection radar (MIMO‐TWDR)recently. When the frequency modulation (FM) sequence of transmission signal is controlled by the chaotic signal, the single‐frequency interference such as the power harmonics sneaking into the phase detector becomes periodical and therefore can be filtered in frequency domain. However, the target echo signal becomes random after chaotic modulation, where the matched filter usually is unable to be realised by Fourier transform and consequently the envelope of direct wave after the phase detector varies stochastically and is difficult to be eliminated by an analogue filter. The FM sequence of random disorganising cannot meet the demand of filtering out the single‐frequency interference and direct wave simultaneously. Therefore, a new method of FM sequence optimisation of chaotic‐based random stepped frequency signal based on genetic algorithm is proposed to solve these problems in this study. Simulations show that the optimised stepped frequency signal possesses the advantages of both chaotic‐based random and linear stepped frequency signal. The proposed scheme achieves excellent performance on direct wave and single‐frequency interference suppression and target detection. Moreover, it can avoid the interference between transmission antennas of MIMO radar.